Correspondências by Rita Azevedo Gomes. The complex hybrid image of contemporary epistolary cinema and contemporary essay film. Issue 4 (20th October 2021) - Monterrubio Ibáñez, Lourdes
Abstract : Rita Azevedo Gomes' Correspondências (2016) draws on the epistolary correspondence between Sophia de Mello Breyner Andresen and Jorge de Sena, as well as their respective poetic works, to build an epistolary-poetic, audio-visual and sensory-emotional kaleidoscope based on their reading, reciting and representation in different languages. In this way, the filmmaker generates a kind of phenomenology of reception that uses all the audiovisual possibilities: the different formats, digital and analogue; their multiple textures; and the diverse options of the texts enunciation. The experimentation with their different combinations, also using various image and sound effects, materialises in an epistolary-poetic essay film which reflects on the aesthetic experience and attains a hybrid, complex image defining contemporary cinema: between person and character, diegesis and extradiegesis, digital and analogue images, voice-in and voiceover, private and public, life and work, present and past, absence and presence, that is, between reproduction and representation. Azevedo's essayistic reflection on creation, exile and absence is generated through parataxic thinking and interstitial thinking that create dialectical and symbolic sentence-images. Thus, Correspondências becomes an avant-garde expression of both contemporary epistolary cinema and contemporary essay film.